Clinical Factors Influencing the Outcomes of an Acellular Dermal Matrix for Skin Cancer Treatment: A Retrospective Study. (July 2020) - Ferrari, Barbara; Reggiani, Camilla; Francomano, Mariangela; Bellini, Pierantonio; Ferrari, Federica; Giacomelli, Luca; Mannocci, Alice; Magnoni, Cristina
ABSTRACT: OBJECTIVE: To evaluate the efficacy and safety of a biologically engineered dermal matrix used in reconstructive surgery after skin tumor resection, focusing on the frequency of successful grafting and identifying potential factors influencing treatment outcomes. DESIGN AND PARTICIPANTS: This retrospective analysis involved consecutive patients diagnosed with skin cancer in any area of the body and for which treatment with a dermal skin template was recommended as alternative to traditional surgery. MAIN OUTCOME MEASURES: Percentage of successful grafting and the patient and tumor characteristics influencing treatment outcome via univariate analysis. MAIN RESULTS: A total of 302 patients were included. Surgical reconstruction with the matrix was effective in 88.9% of the patients within 21 days of surgery. Notably, the matrix was successful regardless of tumor location, type, or size. Infection was the only variable significantly associated with graft failure ( P < .001). CONCLUSIONS: The studied dermal matrix provides an efficient alternative to traditional reconstructive surgery in patients who present specific comorbidities or risk factors. The only variable significantly associated with graft failure was infection, which should be properly controlled through appropriate treatment.